Effect of Topical Application of Chlorogenic Acid on Excision Wound Healing in Rats - Chen, Wei-Cheng; Liou, Shorong-Shii; Tzeng, Thing-Fong; Lee, Shiow-Ling; Liu, I-Min (Planta Medica, 2013)
This study was undertaken to evaluate the therapeutic effects of topical chlorogenic acid on excision wounds in Wistar rats. A 1 % (w/w) chlorogenic acid or silver sulfadiazine ointment was applied topically once a day for 15 days on full-thickness excision wounds created on rats. The 1 % (w/w) chlorogenic acid ointment had potent wound healing capacity as evident from the wound contraction on the 15th post-surgery day, which was similar to that produced by 1 % (w/w) silver sulfadiazine ointment. Increased rates of epithelialization were observed in the treated rats. It also improved cellular proliferation, increased tumor necrosis factor-α levels during the inflammatory phase (12 h, 24 h, 48 h, and 72 h post-wounding) of wound healing, upregulated transforming growth factor-β1 and elevated collagen IV synthesis in the chlorogenic acid-treated group. The results also indicated that chlorogenic acid possesses potent antioxidant activity by increasing superoxide dismutase, catalase, and glutathione, and decreasing lipid peroxidation. In conclusion, these results demonstrate that topical application of chlorogenic acid can accelerate the process of excision wound healing by its ability to increase collagen synthesis through upregulation of key players such as tumor necrosis factor-α and transforming growth factor-β1 in different phases of wound healing as well as by its antioxidant potential.
Keywords: chlorogenic acid; collagen; TGF-β1; TNF-α; wound healing